Determinants of Transitions across Formal / Informal Sectors in Egypt - Aysit Tansel; Zeynel Abidin Ozdemir (Institute for the Study of Labor (IZA), 2015)
Informality is a salient feature of labor market in Egypt as it is the case with many developing countries. This is the first study of the determinants of worker transitions between various labor market states using panel data from Egypt. We first provide a diagnosis of dynamic worker flows across different labor market states. We develop transition probabilities by gender across different labor market states utilizing Markov transition processes. Next we identify the effects of individual, household, job characteristics and location on different mobility patterns by estimating a multinomial logit regression. The results point to the highly static nature of the Egyptian labor market. Government employment and the out of labor force are the most persistent labor market states. Further, only a few of the explanatory variables except high levels of education are found to have predictive power in explaining the transitions from formal wage, informal wage, self-employment, unemployment government employment and out of labor market states.
Keywords: J21; J24; J40; J63; O17; 330; labor market dynamics; informality; Markov processes; multinomial logit; Egypt